The musical temperament psychology and personality of musicians - Kemp, Anthony (Oxford : Oxford University Press, 1996)
Although a kind of folklore has long existed in musical circles relating to personality differences between players of different instruments, this is the first book to examine the impact of personality and temperament on musicianship.
Includes bibliographical references and index.
Keywords: Musicians -- Psychology; Choice (Psychology); Personality and occupation; Muzikantet - Psikologjia - Pesonalitetit -Muzikantet